Polymer, pole piece and related battery monomer, battery and electric device

CN119654362APending Publication Date: 2025-03-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056853.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The active material interface properties of the electrode plates of existing battery cells are poor, resulting in poor cycle performance and storage performance, and are prone to side reactions, affecting the safety performance of the battery.

Method used

Aldehyde and ketone polymers are used as the active material layer in the pole piece. The structure of the polymer is optimized through dynamic frequency scanning tests to reduce the entanglement of molecular chains, form a protective layer, reduce side reactions between active materials and electrolytes, and improve solid performance. Liquid interface properties.

Benefits of technology

It improves the cycle performance and storage performance of the battery cells, reduces the risk of side reactions, and enhances the stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654362A_ABST
    Figure CN119654362A_ABST
Patent Text Reader

Abstract

The invention provides a polymer, a pole piece, a related battery monomer, a battery and an electric device. The polymer comprises an aldehyde ketone polymer, and the aldehyde ketone polymer is prepared into a sheet-shaped structural body; the sheet-shaped structural body is subjected to a dynamic frequency scanning test at (Tm + 20) DEG C to obtain an elastic modulus G '-energy consumption modulus G' curve, the slope of the elastic modulus G '-energy consumption modulus G' curve is K, K is larger than or equal to 0.8 and smaller than infinity, and Tm DEG C represents the melting temperature of the aldehyde ketone polymer. The cycle performance and the storage performance of the battery monomer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Polymers, pole pieces and related battery cells, batteries and electrical devices Technical Field

[0001] The present application relates to the field of batteries, and in particular to a polymer, a pole piece and related battery cells, batteries and electrical devices. Background Art

[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.

[0003] As battery applications expand, the performance requirements for battery cells are becoming increasingly stringent. To improve the safety of battery cells, optimization and improvement of the electrode performance within the cells are common. However, the poor interface properties of the active materials in the electrode currently result in poor cycling and storage performance when applied to battery cells.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a polymer, a pole piece and related battery cells, batteries and electrical devices.

[0006] The first aspect of the present application provides a polymer, which is used in a battery monomer, and the polymer includes an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is subjected to a dynamic frequency sweep test at (Tm+20)°C to obtain an elastic modulus G'-energy loss modulus G" curve, and the slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, and Tm°C represents the melting temperature of the aldehyde-ketone polymer.

[0007] When the polymer of the present application meets the above range, the entanglement state of the molecular chains can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between the molecular chains; moreover, the polymer still maintains a certain molecular chain entanglement state, which can lock the solvent molecules in situ inside the polymer, and can reduce the risk of the polymer dissolving in the electrolyte, thereby improving the stability of the polymer performance; and it is beneficial for the polymer to form a protective layer on the surface of the active material, improve the solid-liquid interface performance, reduce the side reactions between the active material and the electrolyte, and improve the cycle performance and storage performance of the battery cell.

[0008] In some embodiments, 0.8≤K≤100; optionally, 0.8≤K≤10.

[0009] In some embodiments, the aldehyde-ketone polymer has a glass transition temperature (Tg) in °C, where -100 ≤ Tg ≤ 50; alternatively, -80 ≤ Tg ≤ 30. A polymer with a relatively low glass transition temperature has greater molecular chain segment flexibility, making it easier for adjacent molecular chains to be opened.

[0010] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (I),

[0011] In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group; alternatively, R1 includes a single bond, a substituted or unsubstituted C1-C2 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.

[0012] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6),

[0013] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (II),

[0014] In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from integers from 0 to 5, and at least one of r and s is selected from a positive integer; alternatively, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.

[0015] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4),

[0016] In some embodiments, n is a positive integer selected from 500 to 15000; and / or the molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6When the polymer molecular weight is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte while being difficult to be completely dissolved and dispersed by the electrolyte, which is beneficial for regulating the distribution and dispersion of the polymer on the surface of the active material. It can also further improve the flexibility between the polymer molecular chains. The interaction between the molecular chains is relatively weak, which facilitates the solvent molecules in the electrolyte to open the molecular chains, enter between the molecular chains, and be wrapped by the molecular chains. This facilitates the entry of active ions into the active material through the solvent, achieving smooth and rapid migration of active ions.

[0017] The second aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes a positive electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0018] The third aspect of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0019] The fourth aspect of the present application provides a battery cell, which includes a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes the positive electrode sheet as described in any embodiment of the second aspect of the present application; and / or the negative electrode sheet includes the negative electrode sheet as described in any embodiment of the third aspect of the present application.

[0020] A fifth aspect of the present application provides a battery comprising the battery cell as described in the fourth aspect of the present application.

[0021] The sixth aspect of the present application provides an electrical device comprising the battery as described in the fifth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0023] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0024] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .

[0025] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0026] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0027] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0028] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0029] The drawings are not necessarily drawn to scale.

[0030] The following are the descriptions of the reference numerals:

[0031] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0032] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0033] 53. Cover plate;

[0034] 6. Electrical equipment. DETAILED DESCRIPTION

[0035] The following detailed description specifically discloses the embodiments of the polymer, electrode, and related battery cells, batteries, and electrical devices of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0036] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0038] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0039] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0040] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0041] In this application, the terms "plurality" and "multiple" refer to two or more.

[0042] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.

[0043] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.

[0044] The term "hydroxyalkyl" refers to a group in which a hydroxyl group and an alkyl group are connected by a single bond. For example, the hydroxyalkyl group can be a C1 to C8 hydroxyalkyl group, a C1 to C5 hydroxyalkyl group, a C1 to C3 hydroxyalkyl group, or a C1 to C2 hydroxyalkyl group. In some embodiments, the hydroxyalkyl group can include a hydroxymethyl group, a hydroxyethyl group, a hydroxypropyl group, a hydroxybutyl group, or the like. In addition, the hydroxyalkyl group can be optionally substituted.

[0045] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.

[0046] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0047] A battery cell includes a positive electrode plate, a negative electrode plate, and an electrolyte. There is a solid-liquid interface between the plate and the electrolyte, where side reactions may occur, deteriorating the performance of the battery cell. Taking the positive electrode plate as an example, there is a solid-liquid interface between the positive active material contained in the positive electrode plate and the electrolyte. At this interface, the positive active material may undergo side reactions with the electrolyte, resulting in loss of the positive active material and a decrease in the cycle performance of the battery cell. Furthermore, side reactions may produce products that are not conducive to the cycle of the battery cell, thereby deteriorating the storage performance of the battery cell.

[0048] In view of this, the embodiments of the present application improve the interfacial properties of the solid-liquid contact interface to improve the cycling performance and storage performance of battery cells. The embodiments of the present application propose a polymer that, when applied to the positive and / or negative electrode plates, can form an in-situ gel on the surface of the solid-phase active material, i.e., form a stable solid-liquid interface on the surface of the active material, reducing the risk of side reactions at the solid-liquid interface, thereby improving the cycling performance and storage performance of the battery cells.

[0049] polymer

[0050] In the first aspect, the present application proposes a polymer. The polymer is applied to a battery cell, and the polymer includes an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is subjected to a dynamic frequency sweep test at (Tm+20)°C to obtain an elastic modulus G'-energy loss modulus G" curve, wherein the slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, and Tm°C represents the melting temperature of the aldehyde-ketone polymer.

[0051] Specifically, the preparation process of the sheet structure is as follows: the polymer is vacuum dried at 80°C for 12 hours. The dried polymer is hot-pressed into a thin sheet by a flat vulcanizer, the hot pressing temperature is set to (Tm+20)°C, the calendering thickness is 1-2min, the calendering time is 2min, and the pressure is 8MPa. After calendering for 2 minutes, the sample is taken out and placed on another vulcanizer of the same model for cold pressing, and the cold pressing pressure is 10MPa. A fixed-size polymer disc (sheet structure) can be obtained using a circular mold with a diameter of 25mm. For example, the sheet structure can be a disc with a thickness of 1-2mm and a diameter of 25mm; it can also be prepared according to the sample standards required by the test equipment.

[0052] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.

[0053] The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA). The parallel plate had a diameter of 25 mm and a thickness of 0.9 mm. To ensure the test was conducted within the linear tapping region, the strain was 2%, the test temperature was Tm + 20°C, and the frequency sweep range was 500 rad / s ≤ w. 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.

[0054] The dynamic frequency sweep test can characterize the degree of entanglement of the molecular chain under solid phase melting (melt state). Compared with the linear structure or short branched structure, the long branched structure, the network structure and the low cross-linked structure have a high degree of entanglement, which will show a deviation from the linear terminal behavior, and the polymer will show solid phase behavior. When the polymer of the present application meets the above range, the entanglement state of the molecular chain can be further reduced, which is beneficial to the diffusion of the solvent molecules in the electrolyte between the molecular chains; and the polymer still maintains a certain molecular chain entanglement state, which can lock the solvent molecules in situ inside the polymer, and can reduce the risk of the polymer dissolving in the electrolyte, and improve the stability of the polymer performance; and it is beneficial for the polymer to form a protective layer on the surface of the active material, improve the solid-liquid interface performance, reduce the side reactions between the active material and the electrolyte, and improve the cycle performance and storage performance of the battery cell.

[0055] In some embodiments, 0.8≤K≤100; optionally, 0.8≤K≤10.

[0056] Illustratively, K may be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the foregoing values.

[0057] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is Tg, which is expressed in °C, and is -100≤Tg≤50; optionally, -80≤Tg≤30.

[0058] The glass transition temperature is the temperature at which a polymer chain segment transitions from frozen to moving. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature, and the higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured using differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and heat and cool the sample in a nitrogen atmosphere. The sample is heated at a rate of 10°C / min from an initial temperature 20°C lower than the material's intrinsic Tg to a cutoff temperature 20°C higher than the material's intrinsic Tm. The actual glass transition temperature (Tg) and melting temperature (Tm) of the material are determined based on the endothermic and exothermic peaks or transition points of the material during the process.

[0059] The glass transition temperature of the polymer is relatively low, the molecular chain segments are more flexible, and adjacent molecular chains are more easily opened. For example, the glass transition temperature of the aldehyde-ketone polymer can be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.

[0060] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (I),

[0061] In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group;

[0062] Alternatively, R1 includes a single bond, a substituted or unsubstituted C1-C2 methylene group;

[0063] Alternatively, R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.

[0064] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond. For example, R1 is a single bond, which indicates that the carbon atoms on both sides of R1 are connected in the form of a single bond.

[0065] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6),

[0066] Exemplarily, the aldehyde-ketone polymer includes a structural unit represented by formula (II),

[0067] In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from integers from 0 to 5, and at least one of r and s is selected from a positive integer; alternatively, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.

[0068] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4),

[0069] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the interfacial performance of the active material.

[0070] The above polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, enol structural units, acrylonitrile structural units, etc.).

[0071] The groups of the polymers of the present application can be detected by infrared spectrophotometry IR. Specifically, the polymers are tested using a Thermo Nicolet Nexus 670 attenuated total reflection Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.

[0072] The structure of the polymer of the present application can be tested by nuclear magnetic resonance NMR. Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.

[0073] The polymer monomer type of the present application (especially suitable for monomers with a smaller proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific test steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) inlet. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by the flame ionization detector FID or the mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.

[0074] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. These substituents are high-pressure-resistant substituents and are more conducive to stabilizing the structure of the polymer.

[0075] In some embodiments, n is a positive integer selected from 500 to 15,000.

[0076] Optionally, n is selected from a positive integer between 500 and 10,000.

[0077] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.

[0078] When the molecular weight of the polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is conducive to regulating the distribution and dispersion of the polymer on the surface of the active material; and it can further improve the flexibility between the molecular chains of the polymer. The interaction force between the molecular chains is relatively weak, which is conducive to the solvent molecules in the electrolyte opening the molecular chains and entering between the molecular chains and being wrapped by the molecular chains. This is conducive to the active ions entering the active material through the solvent, realizing the smooth and rapid migration of the active ions. For example, the molecular weight of the polymer can be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.

[0079] The molecular weight of a polymer is well known in the art and can be measured using equipment and methods commonly used in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously operate externally for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed. Then, the sample is measured in accordance with GB / T19077-2016 / ISO13320:2009 standard.

[0080] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC instrument (Wyatt Technology Corporation, USA) was used in conjunction with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a ViscoStar II viscometer. The test was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.

[0081] Further research has found that when the polymer also meets one or more of the following conditions, the cycle performance and storage performance of the battery cell can be further improved.

[0082] In some embodiments, the polymer is added to a first solvent at 45°C to form a polymer system. The polymer system is then allowed to stand for 8 hours at 45°C and for ≥24 hours at 25°C. After undergoing these two stages of standing, the polymer system partially transforms in situ into a gel-like substance. The polymer system is then filtered through a 200-mesh filter, leaving the first substance. The mass of the polymer is n, in g; the mass of the first substance is m, in g. The polymer and the first substance satisfy the following conditions: 5 ≤ m / n ≤ 1000; alternatively, 10 ≤ m / n ≤ 1000; further alternatively, 10 ≤ m / n ≤ 50. For example, m / n can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of these values.

[0083] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.

[0084] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include a carbonate solvent, for example, a carbonate solvent including a cyclic carbonate solvent and / or a linear carbonate solvent.

[0085] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.

[0086] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.

[0087] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.

[0088] In this application, m / n is also referred to as the precipitation value, which characterizes the ability of the polymer and solvent to transform into a gel-state substance.

[0089] The first substance mainly includes a gel-state substance formed by a polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.

[0090] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry IR or nuclear magnetic resonance NMR testing shows that the main component of the first substance after drying is the polymer described above.

[0091] By increasing the temperature, this application can achieve stretching of the polymer molecular chains within the safe operating temperature range of the battery cell, promoting mutual attraction and physical bonding between the polymer molecular chains and the solvent. At room temperature, the activity of the polymer molecular segments decreases, maintaining adhesion to the surface of the active material and locking the electrolyte in the spatial environment of the polymer, forming a state similar to in-situ gel. This protects the active material interface while maintaining normal lithium ion transmission, thereby establishing interface protection, reducing surface side reactions, and improving cycling and storage performance.

[0092] Positive electrode

[0093] In the second aspect, the present application proposes a positive electrode plate, which includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes a positive electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0094] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.

[0095] The pole piece can be made by coating a slurry on a current collector, drying it, and cold pressing it. Alternatively, the pole piece can be made from a battery cell. The battery cell is disassembled, and the pole piece soaked in electrolyte is removed from the battery cell. The pole piece soaked in electrolyte is placed under vacuum drying at 100°C for 12 hours to obtain the pole piece, which can be used for pole piece testing such as liquid absorption rate.

[0096] Polymers can be synthesized through emulsion polymerization, suspension polymerization, bulk polymerization, solution polymerization, and other methods. Alternatively, the polymer can be derived from a battery cell. The battery cell is disassembled, and the electrode, which is immersed in the electrolyte, is removed. The active material of the electrode is then peeled off from the current collector by external force to form a powder sample. This powder is then added to DMC and stirred at 80°C for 8 hours at 500 rpm. After stirring, it is allowed to stand at room temperature for 10 minutes. The supernatant is then dried at 80°C for 12 hours to obtain the polymer. The resulting polymer may contain a small amount of lithium salt, but this has little impact on infrared and precipitation value testing. To ensure the accuracy of the polymer, the lithium salt can be further separated by rinsing with DMC at room temperature.

[0097] In some embodiments, the positive electrode active material layer satisfies: v / λ>1.00 Formula (3),

[0098] In formula (1) to formula (3),

[0099] λ represents the porosity of the positive electrode active material layer;

[0100] P1 represents the actual compaction density of the positive electrode active material layer, and its unit is g / cm 3 ;

[0101] P2 represents the actual compaction density of the positive electrode active material, and its unit is g / cm 3 ;

[0102] v represents the liquid absorption rate of the positive electrode active material layer, and its unit is mg / s.

[0103] d represents the diameter of the capillary of the positive electrode active material layer in the capillary test, and its unit is mm;

[0104] h represents the height of the liquid level in the capillary tube, in mm;

[0105] ρ represents the density of the electrolyte in the capillary test, and its unit is g / cm 3 ;

[0106] t represents the time for the electrolyte to be absorbed in the capillary, and its unit is s.

[0107] In this application, the actual compaction density P1 refers to the ratio of the mass of the positive electrode active material layer per unit area to its thickness in the electrode. The actual compaction density is determined by the force of the roller pressing after the electrode is coated, and the unit is g / cm 3 The specific test steps are to take a certain area S of the electrode, weigh the mass M of its positive electrode active material layer, and measure the thickness D of the positive electrode active material layer. The actual compaction density = M / (S×D).

[0108] In this application, the true compacted density P2 refers to the density of the positive electrode active material itself in the positive electrode active material layer; specifically, it refers to the mass of the unit "actual volume of solid material (excluding open and closed pores and pores between particles)" in a dense state. The true volume V is obtained by testing, and the true compacted density is then calculated according to P = m / V. The test can be performed in accordance with GB / T24586-2009; specifically, the test steps are as follows:

[0109] 1) Pretreatment: Place a clean and dry sample cup on a balance, reset it to zero, add the powder sample to the cup, filling it to about 1 / 2 of the cup volume, and record the sample mass.

[0110] 2) Place the sample cup containing the sample in the true density tester, seal the test system, and introduce helium according to the program. By detecting the pressure of the gas in the sample chamber and expansion chamber, the true volume is calculated according to Bohr's law (PV=nRT), and thus the true compacted density is calculated.

[0111] Among them, the volume of the sample cup is: 3.5cm 3 ;Analytical gas: helium.

[0112] Formula (1) can be used to calculate the porosity λ of the active material layer through the actual compaction density and the true compaction density.

[0113] Specifically,

[0114] Wherein, V1 represents the volume of the positive electrode active material layer under mass m, and its unit is cm 3 ;

[0115] V2 represents the volume occupied by active particles in the positive electrode active material layer under mass m, and its unit is cm 3 ;

[0116] m represents the mass of the positive electrode active material layer, and its unit is g.

[0117] Formula (2) can represent the speed at which a certain point of the electrode completely absorbs the liquid (e.g., electrolyte) in the capillary per unit time. In this application, a certain point of the electrode refers to an area of ​​the electrode with a certain area, and its area corresponds to the cross-sectional area of ​​the capillary.

[0118] In this application, the method for detecting the liquid absorption rate of the electrode comprises the following steps:

[0119] A predetermined amount of electrolyte is drawn by a capillary tube;

[0120] The capillary is brought into contact with the electrode, and the electrode to be tested absorbs the electrolyte in the capillary under capillary action;

[0121] After a predetermined time t, the liquid level h of the electrolyte absorbed in the capillary is recorded, and the amount of electrolyte absorbed is calculated based on the liquid level h and diameter d of the capillary and the density ρ of the electrolyte. The liquid absorption rate v of the electrode is quantitatively calculated based on the ratio of the absorbed amount and the predetermined time t.

[0122] Exemplarily, d takes a value of 0.2 to 1, for example, a value of 0.2; h takes a value of 3 to 5, for example, a value of 3.

[0123] The capillary tube has capillary channels that allow it to directly absorb electrolyte through capillary action, without the need for an external drive unit to provide suction power. This allows, on the one hand, more precise control of the amount of electrolyte absorbed through capillary action; on the other hand, because the electrode absorbs electrolyte through its own capillary action, the electrode only draws electrolyte from the capillary tube when the capillary tube contacts the electrode under test. When contact is broken, the electrolyte in the capillary tube stops flowing. Therefore, the amount of electrolyte absorbed in the capillary tube accurately reflects the amount of electrolyte absorbed by the electrode, further improving the accuracy of the test results and enabling quantitative calculation of the electrode's absorption rate.

[0124] This application uses standard electrolyte as the test sample for testing. The specific formula of the electrolyte can refer to the electrolyte formula in the examples.

[0125] Formula (3) represents the liquid absorption rate of the electrode under the porosity λ, which can be used to characterize the liquid absorption speed of the electrode.

[0126] The polymer of the present application is introduced during the preparation process of the active material layer, which can form uniform high wetting points inside the active material layer, uniformly improve the wetting performance of the active material layer, thereby increasing the overall liquid absorption speed of the active material layer, thereby improving the cycle performance of the battery cell using the electrode.

[0127] Optionally, 1.00<v / λ<50.00.

[0128] In some embodiments, 1.00 < v / λ < 4.00; alternatively, 1.20 ≤ v / λ ≤ 3.80; further alternatively, 1.4 ≤ v / λ ≤ 3.6. For example, v / λ can be 1.20, 1.40, 1.80, 2.00, 2.50, 3.00, 3.50, 3.60, 3.80, 3.90, or a range consisting of any two of the above values.

[0129]

[0130] In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the polymer is A%, wherein 0.1≤A≤1.5.

[0131] When the mass percentage of the polymer is within the above range, the interfacial properties of the positive electrode active material layer can be significantly improved. For example, the mass percentage of the polymer can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%,

[0132] 1.2%, 1.5% or a range consisting of any two of the above values.

[0133] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material can include at least one of the following materials: a layered positive electrode active material (such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered, and rock salt phase layered materials), an olivine-type phosphate active material, and a spinel-structured positive electrode active material (such as spinel lithium manganate, spinel lithium nickel manganate, lithium-rich spinel lithium manganate, and lithium nickel manganate, etc.).

[0134] For example, the general formula of the layered positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y is selected from one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 One or more of O2 (NCM523).

[0135] For example, the general formula of the olivine phosphate active material is: Li x A y Me a M b P 1-c X c Y z, wherein, 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A is selected from one or more of Na, K, and Mg; Me is selected from one or more of Mn, Fe, Co, and Ni; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X is selected from one or more of S, Si, Cl, B, C, and N; and Y is selected from one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0136] For example, the general formula of the positive electrode active material of the spinel structure is: Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y is selected from one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0137] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0138] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. This application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.

[0139] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the aldehyde-ketone polymer of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the aldehyde-ketone polymer of the present application, the melting temperature of the positive electrode binder is higher.

[0140] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0141] Negative electrode

[0142] In a third aspect, the present application proposes a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and a polymer, and the polymer comprises the polymer described in any embodiment of the first aspect of the present application.

[0143] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.

[0144] In some embodiments, the negative electrode active material layer satisfies: v / λ>1.00 Formula (4),

[0145] In formula (4),

[0146] λ represents the porosity of the negative electrode active material layer;

[0147] v represents the liquid absorption rate of the negative electrode active material layer, and its unit is mg / s.

[0148] The detection methods of λ and v are as described for the positive electrode active material layer and will not be repeated here.

[0149] In some embodiments, 3.00<v / λ<50.00; alternatively, 3.40≤v / λ≤30.00. For example, v / λ can be 3.20, 3.40, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 8.00, 9.00, 9.50, 10.00, 10.50, 11.00, 12.00, 13.00, 14.00, or a range consisting of any two of the above values.

[0150] In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the polymer is B%, wherein 0.2≤B≤5.0.

[0151] When the polymer content by weight is within the above range, the interfacial properties of the negative electrode active material layer can be significantly improved. For example, the polymer content by weight can be 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or a range consisting of any two of the above values.

[0152] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0153] In some embodiments, the negative electrode active material may adopt a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0154] In some embodiments, the negative electrode active material layer may further include a negative electrode binder. The negative electrode binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0155] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0156] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0157] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the polymer, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0158] battery cells

[0159] In a fourth aspect, the present application provides a battery cell, comprising a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The battery cell is a lithium-ion battery.

[0160] In some embodiments, the positive electrode sheet may be the positive electrode sheet of any embodiment of the second aspect of the present application, thereby improving the cycle performance and storage performance of the battery cell. The negative electrode sheet may be a conventional negative electrode sheet.

[0161] In other embodiments, the negative electrode plate may be any of the negative electrode plates of the third aspect of the present application, thereby improving the cycle performance and storage performance of the battery cell. The positive electrode plate may be a conventional positive electrode plate.

[0162] In some further embodiments, the positive electrode plate can adopt the positive electrode plate of any embodiment of the second aspect of the present application, and the negative electrode plate can adopt the negative electrode plate of any embodiment of the third aspect of the present application, thereby improving the cycle performance and storage performance of the battery cell.

[0163] [Electrolytes]

[0164] Battery cells also include an electrolyte, which conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte; it can be selected based on needs. For example, the electrolyte can be liquid, gel, or solid.

[0165] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0166] As an example, the lithium salt may include a combination of one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0167] As an example, the organic solvent may include a combination of one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0168] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0169] [Isolation film]

[0170] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0171] In some embodiments, the material of the separator can include a combination of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0172] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.

[0173] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.

[0174] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0175] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.

[0176] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.

[0177] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0178] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0179] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0180] Both the battery module 4 and the battery pack can be used as specific examples of the battery of this application.

[0181] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0182] Electrical devices

[0183] In a fifth aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0184] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.

[0185] Example

[0186] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0187] Example 1

[0188] (1) Preparation of positive electrode sheet:

[0189] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0190] A positive electrode slurry is prepared by combining an aldehyde-ketone polymer, the positive electrode active material LiFePO4, a conductive carbon black, a binder such as polyvinylidene fluoride, and N-methylpyrrolidone (NMP). The mass ratio of the aldehyde-ketone polymer, LiFePO4, conductive carbon black, PVDF, and N-methylpyrrolidone (NMP) in the positive electrode slurry is 0.5:96.8:2:0.7:29. The positive electrode slurry is coated on a current collector aluminum foil and dried at 85°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried under vacuum at 85°C for 4 hours to form the positive electrode sheet.

[0191] (2) Preparation of negative electrode sheet:

[0192] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0193] The aldehyde-ketone polymer, artificial graphite (the negative electrode active material), carbon black (the conductive agent), styrene-butadiene rubber (SBR) (the binder), sodium carboxymethyl cellulose (CMC) (the thickener), and deionized water were mixed uniformly in a weight ratio of 2.5:94:0.5:2:1:100 to prepare the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.

[0194] (3) Preparation of electrolyte:

[0195] In an environment with a water content of less than 10ppm, the non-aqueous organic solvents ethylene carbonate EC and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent. Subsequently, the lithium salt LiPF6 and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0196] (4) Preparation of lithium-ion batteries:

[0197] A 16μm polyethylene film (PE) is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide insulation. The electrodes are then wound to form an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. The battery undergoes vacuum packaging, resting, formation, and shaping to produce a lithium-ion battery.

[0198] Comparative Example 1

[0199] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that no aldehyde-ketone polymer was added to the positive electrode plate of Comparative Example 1; and no aldehyde-ketone polymer was added to the negative electrode plate of Comparative Example 1.

[0200] Comparative Example 2

[0201] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the positive electrode and the negative electrode of Comparative Example 2 was replaced with an aldehyde-ketone polymer.

[0202] Example 2 and Example 3

[0203] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the positive electrode and the negative electrode in Examples 2 and 3 was replaced with an aldehyde-ketone polymer.

[0204] Example 4

[0205] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that an aldehyde-ketone polymer was added to the positive electrode plate of Example 4; and no aldehyde-ketone polymer was added to the negative electrode plate of Example 4.

[0206] Example 5

[0207] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that an aldehyde-ketone polymer was added to the negative electrode plate of Example 5; and no aldehyde-ketone polymer was added to the positive electrode plate of Example 5.

[0208] The data of the examples and comparative examples are shown in Table 1.

[0209] Test section

[0210] 1. Lithium-ion battery capacity retention test

[0211] The lithium-ion batteries prepared in the examples and comparative examples were charged to 4.25V at a constant current of 1 / 3C at room temperature, then charged to a current of 0.05C at a constant voltage of 4.25V, left for 5 minutes, and then discharged to 2.8V at 1 / 3C. The resulting capacity was recorded as the initial capacity C0. Then the battery was adjusted to 97% SOC and transferred to a 60°C environment for storage. Repeat the above steps for the same battery, and simultaneously record the discharge capacity Cn of the battery every 30D. The battery capacity retention rate Pn after every 30D is Cn / C0*100%. The five point values ​​of P1, P2...P5 are used as the vertical coordinates, and the corresponding storage time is used as the horizontal coordinates to obtain a dot graph of the battery capacity retention rate and the number of storage days. The battery capacity retention rate data in Table 1 are the data measured after 150D of storage under the above test conditions, that is, the value of P5.

[0212] 2. Lithium-ion battery DC impedance test

[0213] The lithium-ion batteries prepared in the examples and comparative examples were charged at 25°C at a constant current of 1 / 3C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 5 minutes, the voltage V1 was recorded. The batteries were then discharged at 1 / 3C for 30s, and the voltage V2 was recorded. The internal resistance DCR1 of the battery after the first cycle was obtained by calculating (V2-V1) / 1 / 3C. The batteries were charged at a constant current of 1 / 3C to 4.25V at room temperature, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 5 minutes, the batteries were discharged at 1 / 3C to 2.8V. The obtained capacity was recorded as the initial capacity C0. The batteries were then adjusted to 97% SOC and transferred to a 60°C environment for storage. Repeat the above steps for the same battery every 30 days, and record the internal resistance DCRn of the battery for the nth time (n=1, 2, 3...5) at the same time. Use the five point values ​​of DCR1, DCR2, DCR3...DCR5 as the vertical coordinate and the corresponding number of cycles as the horizontal coordinate to obtain a curve graph of the storage days of the battery discharge DCIR.

[0214] In Table 1, the battery internal resistance increase ratio = (DCRn-DCR1) / DCR1*100%. The data in Table 1 are measured after 150D storage under the above test conditions.

[0215] In Table 1, the battery internal resistance increase ratio = (DCRn-DCR1) / DCR1*100%. The data in Table 1 are measured after 150D storage under the above test conditions.

[0216] Test results

[0217] Table 1

[0218] In Table 1, 100% formaldehyde means that the mass percentage of formaldehyde is 100% based on the total mass of monomer 1 and monomer 2.

[0219] 30% polyvinyl alcohol means that the mass percentage of polyvinyl alcohol is 30% based on the total mass of monomer 1 and monomer 2.

[0220] As shown in Table 1, compared to Comparative Example 1, the present embodiment of the present application improves the cycling performance and storage performance of the lithium-ion battery by adding the polymer of the present application to the positive electrode sheet and / or the negative electrode sheet. Compared to Comparative Example 2, the present embodiment of the present application, when satisfying 0.8≤K<∞, especially 0.8≤K≤100, and further, 0.8≤K≤10, has a loose molecular chain arrangement, a small interaction force between the molecular chains, and is easy to open adjacent molecular chains. Chain segment motion is achieved through intermolecular internal rotation, forming a highly flexible molecular chain structure, which can more significantly improve the cycling performance and storage performance of the lithium-ion battery.

[0221] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.

Claims

1. A polymer used in a battery monomer, the polymer comprising an aldehyde-ketone polymer, wherein: The aldehyde-ketone polymer is made into a sheet structure; the sheet structure is subjected to a dynamic frequency scanning test at (Tm+20)°C to obtain an elastic modulus G'-energy loss modulus G" curve, the slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, and Tm°C represents the melting temperature of the aldehyde-ketone polymer.

2. The polymer according to claim 1, wherein 0.8≤K≤100; optionally, 0.8≤K≤10.

3. The polymer according to claim 1 or 2, wherein The glass transition temperature of the aldehyde-ketone polymer is Tg, the unit of which is °C, -100≤Tg≤50; optionally, -80≤Tg≤30.

4. The polymer according to any one of claims 1 to 3, wherein The aldehyde-ketone polymer comprises a structural unit shown in formula (I), In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group; Optionally, R1 includes a single bond, a substituted or unsubstituted C1-C2 methylene group; Alternatively, R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.

5. The polymer according to claim 4, wherein The aldehyde-ketone polymer comprises at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6), 6. The polymer according to any one of claims 1 to 5, wherein the aldehyde-ketone polymer comprises a structural unit represented by formula (II), In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s each independently are integers selected from 0 to 5, and at least one of r and s is selected from a positive integer; Optionally, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.

7. The polymer according to claim 6, wherein the aldehyde-ketone polymer comprises at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4), 8. The polymer according to any one of claims 4 to 7, wherein n is a positive integer selected from 500 to 15000; and / or The molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol. 9 . A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material and a polymer, and the polymer comprises the polymer according to any one of claims 1 to 8 . 10 . A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and a polymer, and the polymer comprises the polymer according to any one of claims 1 to 8.

11. A battery cell, comprising a positive electrode sheet and a negative electrode sheet, wherein: The positive electrode sheet comprises the positive electrode sheet as claimed in claim 9; and / or The negative electrode plate comprises the negative electrode plate as claimed in claim 10.

12. A battery comprising the battery cell according to claim 11.

13. An electrical device comprising the battery as claimed in claim 12.